INTERNATIONAL COOPERATION AND THE LOCAL INTEGRATION OF REFUGEES: A CASE STUDY OF THE MOVERSE PROGRAM AND ACTIONS TO INCLUDE VENEZUELAN WOMEN AND GIRLS IN BRAZIL - Joana D'arc Moreira; Luara Dias dos Santos; Marrielle Ferreira (Revista Tempo do Mundo)
Migration is part of human relations and generates a diversity of changes in the subjectivity of individuals and in host societies, especially in cases of international migration. Furthermore, the mobility experience can be even more difficult if other vulnerabilities are associated with the condition of the migrant subject, such as elements as gender, race, class and age group. Therefore, understanding the difficulties associated with the experiences of women who forcibly migrate, this article seeks to discuss the importance of local integration, specifically efficient labor integration, in guaranteeing rights to these women. These objectives were achieved through the analysis of the performance of the Moverse Program, established through cooperation with several actors, which sought to guarantee the insertion of Venezuelan women in the Brazilian job market. It is worth noting that this study is initial, since the results of Moverse are still in the process of being documented, but, in general, it was noted that women face more difficulties in achieving efficient labor insertion and, consequently, it is necessary to create policies and projects that consider these experiences and create specific solutions to guarantee the effective inclusion of this group. Finally, the initial results demonstrate that projects that consider training Venezuelan women for insertion into the Brazilian job market are fundamental to guaranteeing access to rights in the national territory.